2009
DOI: 10.2334/josnusd.51.37
|View full text |Cite
|
Sign up to set email alerts
|

Localization of impacted maxillary canines using panoramic radiography

Abstract: We aimed to establish a reliable method of localizing an impacted maxillary canine on the sole basis of assessment of a single panoramic radiograph, and to determine the validity and reproducibility of the method. Panoramic radiographs of 50 subjects with a total of 68 impacted canines were analysed. The Canine Incisor Index (CII), Canine Canine Index (CCI), control Canine Incisor Index (c-CII), Zone (apical, middle, coronal) and Sector (I, II, III, IV) were determined on digitized panoramic radiographs. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
25
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 11 publications
6
25
4
5
Order By: Relevance
“…In this study, the root of the ipsilateral incisor was divided into three horizontal zones, and CII of each zone was calculated. The study showed that calculated CII does not vary regarding the zones (21). The results of the Nagpal et al (21) study about magnification were consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…In this study, the root of the ipsilateral incisor was divided into three horizontal zones, and CII of each zone was calculated. The study showed that calculated CII does not vary regarding the zones (21). The results of the Nagpal et al (21) study about magnification were consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 82%
“…The study showed that calculated CII does not vary regarding the zones (21). The results of the Nagpal et al (21) study about magnification were consistent with the results of the current study. In this study, digital panoramic radiography was used as well.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations